Flexibility and Alternative Corporate Strategies - Sefertzi, Elena (Relations industrielles / Industrial Relations, 1996)
This article discusses various and alternative forms of corporate strategy developed with respect to current industrial restructuring and transition towards flexible production. Corporate strategies are distinguished according the size of firms and their organizational structure. The point is not to establish an exhaustive typology of strategies but to elaborate the concept of variety in flexible organization of production and markets. For each type of corporate strategy four major options are analysed: interfirm networks, internal organization of production, labour market, and innovation. The article concludes that the strategic choices made by firms are influenced more by local socioeconomic factors than by global models which apply to all firms ' sites and operations.